The Impact of Visual Communication on Students’ Learning Experience Towards Memory Recognition and Enhancement - Izzatun Nasywa Jamal; Norsimaa Mustaffa (USIM Press, 2024)
AL-I’LAM –J. Contemp. Islam. Comm. & Media Vol. 3, Issue 1 Page (179-196)